Penggunaan Model Pembelajaran Berbasis Proyek terhadap Penguasaan Mufradat Siswa Negeri 1 Sungai Penuh - Ulinnuha, Nur Atika Rima; Muhammad Fadhil Husein (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2024)
This study aims to examine the effectiveness of the Project Based Learning (PjBL) model on the vocabulary (mufradat) mastery of 10th-grade students at MA Negeri 1 Sungai Penuh. Vocabulary mastery is a crucial element in learning the Arabic language, as vocabulary forms the basis of effective communication and deep understanding of texts. This research uses an experimental method by comparing two classes: an experimental class using the PjBL model and a control class using conventional methods. The results show that students in the experimental class demonstrated a significant improvement in vocabulary mastery compared to students in the control class. The study concludes that the application of the PjBL model is effective in enhancing students' Arabic vocabulary mastery